Kajian atas Pemikiran John Wansbrough tentang Al-Qur’an dan Nabi Muhammad - Muhammad Alfatih Suryadilaga (TSAQAFAH, 2011)
The study of Islam among Western thinkers seems not monolithic. In the real of orientalists who use historical analysis to respond Islam with a negative value, such as regarding Islam none more than a Christian heresy. Meanwhile, a positive understanding toward Islam has done by some Islamolog, such as W. Montgomery Watt. The differences are more based on their worldview, phenomenological approach, and interpretations. Then, other understanding of Islam according to sociologists, secularists, humanists, and Western modernists. This article discusses the views of John Wansbrough toward al-Qur’an and the Prophet Muhammad. The study focused on the work of John Wansbrough, entitled “Qur’anic Studies Source and Methods of Scriptural Interpretation”. There are three issues raised in this article: Wansbrough’s view on al-Qur’an, Muhammad prophethood, and Isra’ (nocturnal journey). Regarding to al-Qur’an, wansbrough sees that al-Qur’an has influenced by Jews and Christian, it is fusion of tradition, and even it is the creation of the post-prophetic. Therefore, the critism from other thinkers, such as orientalists as well as coming from Muslims themselves also received a sufficient portion. There are two methods utilized by Wansbrough, historical method and literary analysis. He used historical approach to study the contents of al-Qur’an, and literary analysis to analyze the revealed stories in the Qur’an.